The Yin and Yang of Myeloid Derived Suppressor Cells - Budhwar, Snehil; Verma, Priyanka; Verma, Rachna; Rai, Sangeeta; Singh, Kiran (Frontiers in Immunology, 2018)
In recent years, most of our knowledge about Myeloid derived suppressor cells (MDSCs) has come from cancer studies, which depicts Yin side of MDSCs. In cancer, inherent immunosuppressive action of MDSCs favors tumor progression by inhibiting antitumor immune response. However recently Yang side of MDSCs has also been worked out and suggests the role in maintenance of homeostasis during non-cancer situations like pregnancy, obesity, diabetes and autoimmune disorders. Continued work in this area has armored the biological importance of these cells as master regulators of immune system and prompted scientists all over the world to look from a different perspective. Therefore explicating Yin and Yang arms of MDSCs is obligatory to use it as a double edged sword in a much smarter way. This review is an attempt towards presenting a synergistic coalition of all the facts and controversies that exist in understanding MDSCs, bring them on the same platform and approach their “Yin and Yang” nature in a more comprehensive and coherent manner.